Quality of educational services provided at the Institute of Physical and Sports Education and their relationship to academic excellence from the student’s point of view - Djelti , Tayeb; Bensalem, Khaled (sports creativity, 2023)
The study aims to identify the relationship between the quality of educational services and the academic excellence of students of the Institute of Physical and Sports Education of the University of El Ghaouat. For this purpose, we used a descriptive curriculum on a sample of 112 randomly selected students to collect data. We used a questionnaire tool, after the collection and statistical processing of the results, a correlation between the quality of educational services and academic excellence was reached.